KEARIFAN LOKAL DALAM SISTEM AGROFORESTRI DI KELURAHAN KAMBO KOTA PALOPO - Ibrahim .; Semuel P. Ratag; Euis F. S. Pangemanan (COCOS, 2021)
ABSTRACT This study aims to identify the agroforestry patterns applied by the people of Kambo Village, Palopo City and describe local wisdom in the application of the agroforestry system. This research was conducted in June 2020 in Kambo Village, Palopo City, South Sulawesi. This study used a purposive sampling method by determining the criteria in selecting respondents, namely the respondent is the original community of Kambo Village, the respondent manages agroforestry land, and the respondent is a member of a farmer group Sehati. The results of research on local wisdom in the agroforestry system applied by the community in Kambo Village show that the agroforestry patterns applied by the Kambo Village community are agrisilviculture and apiculture patterns and in the application of the agroforestry system the community still maintains local wisdom that has existed and developed from generation to generation, where It can be seen in some of the activities carried out by the community, such as in seed preparation to harvesting, which still retain the knowledge passed on by their parents for a long time. Keywords : agroforestry, local wisdom. Kambo Village